LOYIHACHILIK FAOLIYATI BO‘LAJAK BOSHLANG‘ICH SINF O‘QITUVCHILARINING PEDAGOGIK VA IJODIY MUVAFFAQIYATLARIGA ERISHISH SHARTI SIFATIDA - Baltamuratova, A.P. (SCIENCE and SOCIETY, 2024)
The article reveals project activities and issues of achieving creative success as a pedagogical process aimed at developing the creative abilities of future primary school teachers.